Outcome of Off Pump and On Pump Coronary Artery Bypass Grafting in Patients with End Stage Renal Disease (Medical Forum Monthly, 2024)
Objective: To study the outcome of, off pump and on pump coronary artery bypass grafting in terms of morbidity and mortality in patients with end stage renal disease (ESRD).Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Department of Cardiothoracic Surgery, Shaikh Zayed Hospital, Lahore from 2014 to 2017.Materials and Methods: The study comprised 52 patients. We divided these patients into two groups; Group:1 (on pump coronary artery bypass grafting) and Group:2 (off pump coronary artery by pass grafting [OPCAB]). We enrolled all patients with chronic kidney disease on maintenance hemodialysis, those needed coronary artery bypass grafting.Results: There was no significant demographic difference in both groups preoperatively. Triple vessel coronary artery disease (CAD) was present in 28 (53.8%)patients; double vessel CAD was present in 18 (34.6%) patients and sever left main CAD was present in 6 (11.5) patients. Peroperatively 3.5 and 3 number of grafts were used in-group:1 and group :2 respectively. Number of blood and blood products were used more in group:1 as compare to group:2.The use of inotropic support and Intra aortic balloon pump (IABP) was significantly higher in group:1.We found increased extubation time, ICU stay and hospital stay in group:1 as compare to group:2.Early postoperative mortality in group:1 and group:2 was 7.7% and 3.8% respectively. Six months survival rate was equal in both groups.Conclusion: Off pump coronary artery bypass grafting is encouraging operative strategy in patients with End stage renal disease. In this technique less number of blood and blood products are used and it has lower morbidity, mortality and hospital stay.